Angkringan sebagai Daya Tarik Generasi Baby Boomers - Luh Surya Dewi (Universitas Pendidikan Nasional, 2019)
ABSTRACT This study examines the interest of the baby boomer generation into angkringan consumers. The concept of culinary attraction includes diversity of culinary activities, typical food, convenient and clean location, unique and attractive venue design, good service, competitive market, price and value proportion, opportunity to socialize, cultural interaction with culinary, Family atmosphere, attractive environment, traditional, national and international products. The informants used in this study were eight informants, namely four baby boomer customers and four angkringan owners. Data collection is done by interviews, observation and documentation. Data analysis techniques are used to analyze qualitative method data. This study concluded that not only the millennial generation was affected by globalization. This can be seen from the millennial lifestyle style that mostly hang out, chat with friends and gatherings, but baby boomers also enjoy the influence of globalization. There are also many baby boomers who do the same thing, like hanging out at the end, gathering with friends and reunions and enjoying the moment or the past. This research is useful for customers and sellers that globalization not only has a negative influence but also a positive influence, one of which is like hanging out. It's a life style or western lifestyle. While drinking while hanging out, chatting and gathering. Can remember the past and get back or repeat the first moments.